2018
DOI: 10.5271/sjweh.3726
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged sitting at work is associated with a favorable time course of low-back pain among blue-collar workers: a prospective study in the DPhacto cohort

Abstract: Sitting at work is suggested to increase risk for low-back pain (LBP). Thus, an association between temporal patterns of sitting and time course of LBP, across 12 months, among 665 participants from the DPhacto cohort was conducted. We found that longer durations of total and temporal sitting periods at work were significantly associated with a favorable time course of LBP.Affiliation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
(68 reference statements)
1
27
0
3
Order By: Relevance
“…After duplicate removal, 897 papers were screened at title/abstract level and 49 full-text articles were assessed for eligibility. In total, 10 articles were included, of which eight investigated the prospective association between physical behaviour and the risk of NP and/or LBP (Ariens et al, 2001;Ariens, Bongers, Hoogendoorn, Wal, & Mechelen, 2002;Hallman, Birk Jorgensen, & Holtermann, 2017;Hallman et al, 2016;Korshøj et al, 2018;Lunde, Koch, Knardahl, & Veiersted, 2017;Sitthipornvorakul, Janwantanakul, & Lohsoonthorn, 2015;Thiese, Hegmann, Garg, Porucznik, & Behrens, 2011), and two articles investigated the effect of physical behaviour on prognosis of LBP (Bousema, Verbunt, Seelen, Vlaeyen, & Knottnerus, 2007;Hendrick et al, 2013). Table 1 provides the main characteristics of the included articles.…”
Section: Search Results and Selection Of Articlesmentioning
confidence: 99%
“…After duplicate removal, 897 papers were screened at title/abstract level and 49 full-text articles were assessed for eligibility. In total, 10 articles were included, of which eight investigated the prospective association between physical behaviour and the risk of NP and/or LBP (Ariens et al, 2001;Ariens, Bongers, Hoogendoorn, Wal, & Mechelen, 2002;Hallman, Birk Jorgensen, & Holtermann, 2017;Hallman et al, 2016;Korshøj et al, 2018;Lunde, Koch, Knardahl, & Veiersted, 2017;Sitthipornvorakul, Janwantanakul, & Lohsoonthorn, 2015;Thiese, Hegmann, Garg, Porucznik, & Behrens, 2011), and two articles investigated the effect of physical behaviour on prognosis of LBP (Bousema, Verbunt, Seelen, Vlaeyen, & Knottnerus, 2007;Hendrick et al, 2013). Table 1 provides the main characteristics of the included articles.…”
Section: Search Results and Selection Of Articlesmentioning
confidence: 99%
“…Over 70% of physiotherapists considered the upright lordotic sitting posture as the optimal posture (82). Major stakeholders in the healthcare systems around the world commonly agree that prolonged sitting is associated with a higher prevalence of LBP (25,(83)(84)(85)(86)(87)(88). Sustained sitting for more than thirty minutes is considered a common aggravating factor for many people with LBP (81), although there is a lack of evidence in support of this concept (89)(90)(91).…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantage of prolonged sitting are increased intra-disc load, weakened posterior lumbar structures, and decreased metabolic exchange [ 25 ]. A previous study suggested that prolonged sitting is a risk factor for LBP [ 26 ]. However, the systematical study does not support the idea that prolonged sitting at work and during leisure time is related to LBP [ 6 ].…”
Section: Discussionmentioning
confidence: 99%